2012
DOI: 10.1021/tx3000329
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexyl Analogues of Ethylenediamine Dipropanoic Acid Induce Caspase-Independent Mitochondrial Apoptosis in Human Leukemic Cells

Abstract: We investigated the cytotoxicity of recently synthesized (S,S)-ethylendiamine-N,N'-di-2-(3-cyclohexyl)propanoic acid esters toward human leukemic cell lines and healthy blood mononuclear cells. Cell viability was assessed by acid phosphatase assay, apoptosis, and differentiation were analyzed by flow cytometry and electron microscopy, while intracellular localization of apoptosis-inducing factor (AIF) was determined by immunoblotting. It was demonstrated that methyl, ethyl, and n-propyl esters were toxic to HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The antileukemic action of cyclohexyl analogues, esters ( L 2 – L 5 ) of ethylenediamine dipropanoic acid ( L 1 ),has been previously reported, with L 3 marked as the most potent ligand and the HL‐60 cell line as the most sensitive to its cytotoxic action . In the present study, human promyelocytic cell line (HL‐60) was also the most sensitive to antitumor action of all investigated substances.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The antileukemic action of cyclohexyl analogues, esters ( L 2 – L 5 ) of ethylenediamine dipropanoic acid ( L 1 ),has been previously reported, with L 3 marked as the most potent ligand and the HL‐60 cell line as the most sensitive to its cytotoxic action . In the present study, human promyelocytic cell line (HL‐60) was also the most sensitive to antitumor action of all investigated substances.…”
Section: Resultssupporting
confidence: 57%
“…The treatment with C3 complex (4 hr, 18 μ m ) caused more pronounced increase in DHR‐derived FL1 fluorescence compared with novel complexes (Figure a), suggesting that C3, despite the lack of noticeable increase in superoxide production (Figure b), induces rapid and prominent oxidative damage in HL‐60 cells, as observed previously in U251 glioma cells . On the other hand, it was shown that organic ligand induced mitochondria‐derived superoxide hyperproduction in HL‐60 cells, unlike cisplatin, indicating that cyclohexyl‐functionalized edda ligands significantly contributed to mitochondria‐derived oxidative damage.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…[6] In contrast to cisplatin, these complexes mostly cause rapid, caspase-independent, oxidative stressmediated, non-apoptotic cell death characterized by massive cytoplasmic vacuolization, cell membrane damage and the absence of protective autophagy. [7,8] Indeed, organic ligands themselves exert significant in vitro toxicity probably due to an incorporated ethylenediamine group, which is known for its positive contribution to the cytotoxicity effect. [9] Ethylenediamine-N,N′-di-3-propanoate (R 2 eddp)-type esters such as diisopentyl-, di-n-butyl-and di-n-pentyl-(S,S)-ethylenediamine-N,N′-di-2-propanoate show even higher cytotoxicity and better selectivity against cervix adenocarcinoma cell line (HeLa), human melanoma (Fem-x) and human chronic myelogenous leukaemia (K562) cells in comparison to cisplatin.…”
Section: Introductionmentioning
confidence: 99%